Identificação e avaliação de áreas potenciais de uso agrícola do lodo de Estações de Tratamento de Esgoto Sanitário nas bacias dos rios Velhas, Jequitaí e Pacuí - Lucas de Almeida Chamhum Silva (2018)
Sewage sludge corresponds to the solid material generated in sewage treatment plants, which can be considered waste or by-product from this process. As by-product, some alternatives may be adopted for its use, especially its use as organic fertilizer and soil amendment, due to its high content of organic matter and nutrients. Although widely spread and well established, especially abroad, the use of this practice in Brazil is still rare. This is possibly due to strict legal criteria currently in place (established in CONAMA Resolution 375/2006) and the social perception about the agricultural use of sludge. In this context, the objective of this study was to identify sewage treatment plants (STP) currently in operation in two watersheds, Velhas river and Jequitaí, Pacuí and São Francisco rivers, and evaluate sludge generation and disposal in these watersheds. In addition, a map of suitable areas for sludge disposal was created, based on agricultural use potential. The map could be used as a decision-making tool for sewage sludge disposal. Finally, the acceptance and attitudes of farmers towards the use of sludge in agroforestry activities was assessed in a focus group. To carry out this research, operational data from STPs and geospatial data related to soil properties, land use and topography were obtained and manipulated on Geographic Information System (GIS). A pilot focus group comprised of 7 farmers from 3 different municipalities was performed. 70 STPs were identified as currently in operation in both watersheds, with a population equivalent above 4 million inhabitants. A sludge production of 81,000 m³.year-1 was estimated. Approximately 77% of sludge is disposed on sanitary landfills. Suitability analysis of areas for sludge application showed that almost 4% of the total area was classified as level I (the level of suitability); 10% as level II; 20% as level III; 13% as level IV and 52% as level V (unsuitable areas). The focus group indicated greater resistance to sludge application on vegetables, due to the possibility of direct contact of the edible part of the plant with the sludge. Forestry, reclamation of degraded land and long-term crops, in which there is no direct contact of the sludge with the plant, were identified as potentially receiving activities for sludge.